Manajemen Komunikasi Universitas Negeri Surabaya dalam Implementasi Rekognisi Pembelajaran Lampau Untuk Meningkatkan Kompetensi Perangkat Desa - Dharmawan, Awang; Lolita, Yuri (Universitas Negeri Surabaya, 2024)
The State University of Surabaya (UNESA), the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration, and the Bojonegoro Regency Government initiated an RPL program collaboration, offering opportunities to all village officials in Bojonegoro Regency who have not yet obtained a bachelor's degree to have their various experiences and work portfolios assessed against the learning outcomes of courses in higher education. This RPL program, specifically for village officials, is the first of its kind in Indonesia. So, it encourages researchers to use case study research methods. This research discusses the importance of communication management, as many actors and institutions within UNESA are responsible for implementing this RPL collaboration. The students from village officials studying at the undergraduate level in five study programs selected by UNESA. UNESA's communication management in managing RPL is evident in the inter-institutional communication content that regulates their respective duties and functions, so these institutions structurally have a coordinating function and are responsible to the Rector. The communication flow between institutions within UNESA is formally regulated, and its channels are written. Conversely, in the classroom between lecturers and RPL students, communication management is more equal in community service and joint research programs.